Tom Sawyer abroad ; Tom Sawyer, detective - Twain, Mark, 1835-1910 (Mark Twain Library., 2011)
These unjustly neglected works are among the most enjoyable of Mark Twain's novels. Tom Sawyer Abroad sets the three characters so popular in Adventures of Huckleberry Finn--Tom Sawyer, Huckleberry Finn, and Jim--and sends them on a balloon trip to Africa. The balloon has wings and fans which can propel it a hundred miles an hour in still air and three hundred miles an hour with a stiff tail wind. Tom is again the manager, the one with information and imagination. Huck is still the one with a literal mind and common sense, and Jim, though the oldest, is once more the most limited in experience and the most burdened by superstition. Tom Sawyer, Detective is not only a detective story but also a burlesque of detective stories. Tom Sawyer and Huckleberry Finn perform throughout as a youthful imitation of the immensely popular Sherlock Holmes, with Huck as a counterpart of Dr. Watson. To everyone's wonderment Tom deduces who the murderer is, and Huck catches the spirit of the whole when he says "Well, sir, if there'd been a brass band to bust out some music, then, it would 'a' been just the perfectest thing I ever see, and Tom Sawyer he said the same."